Adsorption of phosphates from water by two polymer-silicate composites. Issue 4 (26th August 2020) - Wijesinghe, Kalpani E. H.; Dissanayake, Rasika E. A.; Iqbal, Sithy S.; Priyantha, Namal; Iqbal, Mohamed C. M.
Abstract: Phosphorus is an essential plant nutrient required by all living organisms and global phosphate resources, being finite, are expected to last another 125 years. This study investigated a sustainable approach to retrieving phosphates from aqueous media using a composite of commonly available biological and mineral sources. Two composites were synthesized using (i) feldspar, alginate, and agar cross-linked by ferric and calcium ions (FAA), and (ii) feldspar, fly ash, and alginate crosslinked with copper ions (FFA). Adsorption parameters were determined using a synthetic phosphate solution. The FAA composite adsorbed 69% of the phosphates within 4 hours; 81% was adsorbed after equilibrium was reached in 9.5 h (pH 4–10). The FFA composite adsorbed 82% of the phosphate reaching equilibrium after 5.5 h (pH 3–7). Characterization of the composite by scanning electron microscopy and Fourier Transform Infrared spectroscopy showed the presence of inorganic and organic functional groups in the agar and alginate that could adsorb phosphate ions. The kinetic and isotherm data suggest that the phosphate ions migrate to the composite boundary and are precipitated by the Ca 2+, Fe 3+, and Cu 2+ in the composite matrix. Once the outer composite is saturated, the rest of the phosphate ions are entrapped by the biopolymers through H and covalent bonding. These two biopolymer composites can be easily synthesized and scaled up for phosphate adsorption. Recovery of the adsorbed phosphates, in future studies, can be used for plant nutrition to complete the open-ended cycle of phosphates leaching into water bodies.